On the performance of reconfigurable intelligent surface-assisted UAV-to-ground communication systems - Duong Huu Ai; Van Loi Nguyen; Hoang Huu Duc; Khanh Ty Luong (Universitas Ahmad Dahlan, 2023)
In this study, to reduce the average symbol error rate, and improve coverage and reliability of unmanned aerial vehicles (UAVs) to ground communication systems. In this case, we propose a reconfigurable intelligent surfaces (RISs) assisted for UAV to ground communication scheme, where radio frequency (RF) signal generator sends an unmodulated carrier signal from UAVs to the RIS. At reconfigurable intelligent surface, the RIS modulates each signal, and RIS is as a signal generator. We carry out a performance analysis of UAV-to-ground communication systems with RIS-assisted and without RIS for subcarrier quadrature amplitude modulation (SC-QAM) technique. The analytical expressions of average symbol error rare (ASER) and average channel capacity (ACC) is derived. From the results, it is show that with RIS assisted can effectively improve the reliability and coverage of the UAVs to ground communication systems.